Integration of Religious Moderation in Developing an Islamic Religious Education Curriculum - Imamah, Yuli Habibatul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to explain the integration of various modes in developing an Islamic religious education curriculum. This type of research is qualitative with a research library approach. Research data consists of data on religious moderation, curriculum development, and PAI material from primary sources in the form of relevant books and journals. Data collection techniques are carried out using documentation. The researchers' data sources were obtained from books and journals about religious moderation, curriculum development, and PAI materials. Data analysis uses Content Analysis. Based on the research results obtained, the integration of religious moderation in the Islamic religious education curriculum has the potential to produce education that is more inclusive, tolerant, and respectful of diversity of beliefs. A curriculum development process that considers principles of religious moderation tends to create a learning environment that is more open to interreligious dialogue and better understanding between religious groups. The importance of training for teachers and education stakeholders in implementing the integration of religious moderation in Islamic religious education practices. Periodic evaluation of the curriculum that has been integrated with various moderations needs to be carried out to ensure that integration goals are achieved and are in line with societal developments. This research results provide recommendations for stakeholders in Islamic religious education to adopt and develop a diverse moderation approach in curriculum as a step towards a more harmonious and inclusive society. Thus, this conclusion shows that the integration of religious moderation in developing an Islamic religious education curriculum can make a positive contribution to creating more inclusive and tolerant education, as well as encouraging better understanding between religious groups. In addition, this research also highlights the importance of training and sustainability evaluation in carrying out this integration effectively.